The story of your city (Volume 1) - Moonen, Tim (European Investment Bank, 2018)
By the end of this century, 9 out of 10 Europeans will live in an urban area. But what kind of city will they call home? You'll find all the answers in CITY, TRANSFORMED, the new essay series from the European Investment Bank. This panoramic first essay in the series lays out a great sweeping history of European cities over the last fifty years-and showcases new directions being taken by some of our most innovative cities. Urban experts Greg Clark, Tim Moonen, and Jake Nunley based at University College London take a definitive look at how Europe's cities transformed from post-industrial decline to thriving metropolises that are as prosperous and liveable as anywhere on Earth.